Remedial Measures for Challenges Faced by Agriculture Sector in Developing Countries - Dwivedy, Nidhi (Indian Farming, 2015)
Whether it was substitence farming in the sixties or Commercial farming starting in the eighties in India, agricultural sector has always faced challenges, in various forms. But with the backing of technology and previous experiences it can be said that certain ways when followed in farming have proved to be beneficial for this sector as well as to the farming comminty. For example, Integrated Farming Systems, Rain water harvesting, Organic farming are some of the best proven ways that if followed sustain agriculture.